Oncologic treatment strategies and relative survival of patients with stage I–III rectal cancer - A EURECCA international comparison between the Netherlands, Belgium, Denmark, Sweden, England, Ireland, Spain, and Lithuania. Issue 9 (September 2018) - Breugom, A.J.; Bastiaannet, E.; Boelens, P.G.; Van Eycken, E.; Iversen, L.H.; Martling, A.; Johansson, R.; Evans, T.; Lawton, S.; O'Brien, K.M.; Ortiz, H.; Janciauskiene, R.; et al.
Abstract: Introduction: The aim of this EURECCA international comparison is to compare oncologic treatment strategies and relative survival of patients with stage I–III rectal cancer between European countries. Material and methods: Population-based national cohort data from the Netherlands (NL), Belgium (BE), Denmark (DK), Sweden (SE), England (ENG), Ireland (IE), Spain (ES), and single-centre data from Lithuania (LT) were obtained. All operated patients with (y)pTNM stage I-III rectal cancer diagnosed between 2004 and 2009 were included. Oncologic treatment strategies and relative survival were calculated and compared between neighbouring countries. Results: We included 57, 120 patients. Treatment strategies differed between NL and BE (p < 0.001), DK and SE (p < 0.001), and ENG and IE (p < 0.001). More preoperative radiotherapy as single treatment before surgery was administered in NL compared with BE (59.7% vs. 13.1%), in SE compared with DK (55.1% vs. 10.4%), and in ENG compared with IE (15.2% vs. 9.6%). Less postoperative chemotherapy was given in NL (9.6% vs. 39.1%), in SE (7.9% vs. 14.1%), and in IE (12.6% vs. 18.5%) compared with their neighbouring country. In ES, 55.1% of patients received preoperative chemoradiation and 62.3% postoperative chemotherapy. There were no significant differences in relative survival between neighbouring countries. Conclusion: Large differences in oncologic treatment strategies for patients with (y)pTNM I-III rectal cancer were observed across European countries. No clear relation between oncologic treatment strategies and relative survival was observed. Further research into selection criteria for specific treatments could eventually lead to individualised and optimal treatment for patients with non-metastasised rectal cancer.